2019
DOI: 10.1186/s12884-019-2592-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting uptake of ≥ 3 doses of Sulfadoxine-Pyrimethamine for malaria prevention in pregnancy in selected health facilities, Arusha region, Tanzania

Abstract: BackgroundTanzania adopted the revised World Health Organization policy in 2013 recommending a minimum of ≥3 doses of Intermittent Preventive Treatment during pregnancy with Sulfadoxine-Pyrimethamine (IPTp-SP) to protect against malaria. A study in Tanzania in 2014 reported low (9%) uptake. We investigated health workers knowledge about IPTp-SP and factors that influenced uptake of > 3 doses of IPTp-SP among pregnant women.MethodsWe conducted a cross-sectional study in 2017 among post-delivery women and health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
28
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 18 publications
11
28
4
Order By: Relevance
“…The high prevalence of the optimal uptake of IPTp-SP in this study is consistent with other studies in Ghana and Sierra Leone (21,22,25). However, other studies in Uganda, Tanzania and Malawi that investigated the optimization of IPTp-SP found low uptake levels of IPTp-SP3 + doses (19,20,32). The high prevalence of optimal IPTp-SP could be attributable to the sustained efforts by the Kenyan government and development partners towards the elimination of MiP and continued investment in maternal health.…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of the optimal uptake of IPTp-SP in this study is consistent with other studies in Ghana and Sierra Leone (21,22,25). However, other studies in Uganda, Tanzania and Malawi that investigated the optimization of IPTp-SP found low uptake levels of IPTp-SP3 + doses (19,20,32). The high prevalence of optimal IPTp-SP could be attributable to the sustained efforts by the Kenyan government and development partners towards the elimination of MiP and continued investment in maternal health.…”
Section: Discussionsupporting
confidence: 91%
“…In this study it was established that knowledge in terms of awareness of signs of malaria (χ 2 = 1.890, df = 2, p = .389), knowledge of fansidar in preventing malaria (χ 2 = 1.166, df = 1, p = .280) and knowledge on effects of malaria (χ 2 = .060, df =2, p = .970) did not significantly influence IPTp3+ Uptake among pregnant mothers. This result is different from those in a study which was done in Tanzania by (Mchwampaka et al, 2019) that mothers did not like taking Fansidar because of its associated side effects such as nausea. Such contradictions could be perhaps attributed to the fact that benefits of IPTp3+ exceed the side effects if well known by the pregnant mothers themselves.…”
Section: Knowledge Factors and Uptake Of Iptp3+contrasting
confidence: 98%
“…Health workers being knowledgeable, and this only benefits the women who attained ANC (15). Findings from Ghana cost of services, distance to facility, Level of education, ANC schedule (16), (17).Distance to the health facility, pregnancy disclosure is among factors that affect ANC attendance and uptake of IPT3 (9).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that educated and wealthier women were knowledgeable about IPTp and more likely to receive the SP [ 18 ]. Also, the uptake of SP was higher for women who attended 3 to 4 ANC visits and started ANC visits in their first or second trimester compared to those who started in the third trimester [ 13 , 16 , 17 , 19 ].…”
Section: Introductionmentioning
confidence: 99%